2014
DOI: 10.1007/s10389-014-0631-x
|View full text |Cite
|
Sign up to set email alerts
|

Internet use among mothers of young children in Norway—a survey of Internet habits and perceived parental competence when caring for a sick child

Abstract: Aim The Internet has become the leading source of child health information for parents. Perceived parental competence, self-efficacy, education and satisfaction with traditional health services may influence Internet use. The aim of study was to investigate the interplay between these factors. Subject and methods A survey that included 99 Norwegian mothers to young children was conducted to assess the relationship between Internet use concerning child health, perceived parental competence, self-efficacy and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 26 publications
8
26
0
3
Order By: Relevance
“…The use of either digital media or personal contacts does not significantly vary between the information seeking targets, general health and development and acute child's illness. Comparable results were found in a study on Norwegian mothers [36].…”
Section: Discussionsupporting
confidence: 74%
“…The use of either digital media or personal contacts does not significantly vary between the information seeking targets, general health and development and acute child's illness. Comparable results were found in a study on Norwegian mothers [36].…”
Section: Discussionsupporting
confidence: 74%
“…The use of either digital media or "personal contacts" does not signi cantly vary between the information seeking targets, general health and development and acute child's illness. Comparable results were found in a study on Norwegian mothers [36].…”
Section: Discussionsupporting
confidence: 74%
“…In addition to offline resources, resources on the Internet have provided greater public access to health information. Previous studies (Allen and Rainie 2002;Fox and Duggan 2013;Skranes et al 2014;Yoo 2004) showed that mothers are the most fervent online health information seekers related to family members including their children. For this study, mothers were selected as the target population in consideration of their key roles as health-information seekers, health-managers and caregivers for their family members and themselves.…”
Section: Introductionmentioning
confidence: 99%